2008
DOI: 10.1111/j.1651-2227.2008.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth and maternal smoking in pregnancy are strong risk factors for aortic narrowing in adolescence

Abstract: Aim: Preterm transition from foetal to neonatal circulation might permanently alter aortic growth and development. To test this hypothesis, we measured aortic dimensions in adolescents born very preterm.Methods: Eighty-six healthy 15-year-old subjects were studied; 45 born very preterm at an average gestational age of 28 weeks (birth weight < 1500 g) and 41 controls born at term. Using a pulsegated Fiesta sequence on a 1.5T MR-scanner, 25 images were collected within the heart cycle at several levels of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 33 publications
4
22
1
Order By: Relevance
“…Baseline echocardiographic results were similar to those in previously published studies [14,15] which revealed smaller heart (LV, RV and LA) dimensions in the group of ELBW children than in the control group. After expressing the results as z-scores for BSA, statistically significant differences were observed for diastolic diameters of both ventricles and the volume of the left one.…”
Section: Discussionsupporting
confidence: 81%
“…Baseline echocardiographic results were similar to those in previously published studies [14,15] which revealed smaller heart (LV, RV and LA) dimensions in the group of ELBW children than in the control group. After expressing the results as z-scores for BSA, statistically significant differences were observed for diastolic diameters of both ventricles and the volume of the left one.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have demonstrated higher BP in children and young people born preterm, although the effects of gestational age, birthweight and intrauterine growth on later BP varied between studies . It is clear that the early life environment may trigger structural and functional changes in cardiovascular, metabolic and neuroendocrine function that persist throughout life .…”
Section: Discussionmentioning
confidence: 99%
“…A control group of 125 children, born at full term, was assembled from a population‐based register and matched according to birth date, birth hospital and gender. In 2005 and 2006, study subjects and controls were invited to participate in one or two MRI studies that were performed at the same time, one investigating the brain and one measuring the aorta . This meant that 76 of the 182 VLBW children underwent an MRI examination at the age of 12–17 years.…”
Section: Methodsmentioning
confidence: 99%
“…An initial study conducted by Edstedt Bonamy et al examined adolescent girls born preterm (≤34 weeks’ gestational age) and reported narrower, but more compliant abdominal aortae and lower peripheral skin blood flow compared with girls born at term. Follow‐up MRI analysis conducted in preterm adolescent boys and girls demonstrated a 16% narrowing in the thoracic aorta and a 19% narrowing of the abdominal aorta in the individuals born preterm, after correcting for body size and gender . There was also a 7% mean reduction in the number of capillaries per mm 2 of skin in the fingertip (as assessed using intra‐vital microscopy), which likely accounts for the reduced peripheral skin blood flow .…”
Section: Introductionmentioning
confidence: 94%
“…Of concern, there is now increasing evidence linking preterm birth with an increased risk of cardiovascular disease as the first survivors of very and extremely preterm birth reach early adulthood. Numerous studies have reported that preterm birth is a strong risk factor for increased arterial pressure in children , adolescents , young adults and older adults . This is of considerable clinical relevance given that elevated arterial pressure is a major risk factor for the development of cardiovascular disease and adverse cardiovascular events such as myocardial infarction and stroke .…”
Section: Introductionmentioning
confidence: 99%